1981
DOI: 10.1901/jeab.1981.35-187
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Schedules of Signaled Appetitive Events Over Schedules of Unsignaled Ones

Abstract: Two experiments were completed allowing albino rats to choose between signaled and unsignaled reward conditions. These experiments examined the effects on preference of (1) response dependent versus response-independent reward and, (2) food pellets versus chocolate milk as the reward. All subjects preferred the signaled condition over the unsignaled condition, whether exposed to response-dependent, or to response-independent delivery of rewards. Preference was controlled most effectively by presenting both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
28
2
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 16 publications
7
28
2
1
Order By: Relevance
“…No prefood signal was available during the unsignaled schedule. Three subjects were tested using a commitment procedure (see below) identical to that used in Badia et al (1981) with the exception that the response initiating the changeover condition was a shuttle response and not a lever-press response. Two additional subjects were tested using a noncommitment procedure similar to Experiment 1.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…No prefood signal was available during the unsignaled schedule. Three subjects were tested using a commitment procedure (see below) identical to that used in Badia et al (1981) with the exception that the response initiating the changeover condition was a shuttle response and not a lever-press response. Two additional subjects were tested using a noncommitment procedure similar to Experiment 1.…”
Section: Methodsmentioning
confidence: 99%
“…These results indicate that the discrepant findings of earlier studies are due to procedural differences involving signal duration and choice commitment. The data are consistent with a conditioned reinforcement interpretation of choice.Key words: choice, signaling, food, shuttle response, ratsSeveral investigators have reported that subjects prefer signaled food schedules over unsignaled ones (e.g., Badia, Ryan, & Harsh, 1981;Lewis, Lewin, Muehleisen, & Stoyak, 1974;Ryan & Badia, 1982). Lewis et al (1974), for example, found that pigeons acquired a keypeck changeover response that converted an unsignaled variable-interval food schedule to a signaled one for 1-min periods.…”
mentioning
confidence: 99%
See 3 more Smart Citations